Thyrotoxicosis: A rare cause of dysphagia - A. M. B. D. Alahakoon; W. W. L. A. Jayanaga (Sri Lanka Journal of Medicine, 2023)
Excess and deficiency of thyroid hormones can have a variety of gastrointestinal manifestations ranging from heartburn, dysphagia, vomiting, diarrhea to constipation. We present a case of chronic thyrotoxic myopathy presenting as generalized weakness with bulbar involvement. He made a complete recovery with antithyroid therapy.